Pendekatan Edukatif Komunikasi Keagamaan Hindu di Era Digital Tinjauan Literatur Sistematis - Dana, I Wayan; Masriastri, I Gusti Ayu Ketut Yuni; Nurlensi, Nurlensi (Fakultas Dharma Duta, 2025)
The digital era has fundamentally transformed religious communication, shifting interactions from physical spaces to virtual platforms. This article systematically reviews the literature to analyze how educative approaches are implemented in Hindu religious communication within the Indonesian digital ecosystem, focusing on the YouTube platform. The core research question addresses the different educative strategies employed by both institutional and individual Hindu religious actors. Using a qualitative content analysis of literature from the last three years (2023-2025), this study maps the characteristics, strategies, and challenges of digital religious communication. The findings reveal a clear divergence in these educative approaches. Institutional actors (e.g., PHDI, Bimas Hindu) tend to use a formal-informative approach, leveraging digital media for program dissemination and organizational documentation through a monologic communication model. In contrast, charismatic individual figures (e.g., Ida Pandita Mpu Jaya Acharya Nanda) utilize a personal-dialogic approach that focuses on in-depth theological education, pastoral guidance, and interactive community engagement. This phenomenon points to a significant decentralization of religious authority, where digital platforms facilitate the rise of new knowledge centers outside of formal structures. The primary challenge lies in maintaining theological depth amid the demands of digital media engagement while also bridging the digital literacy gap within the community.